Pengaruh Sikap Terhadap Tindakan Mahasiswa Dalam Pencegahan Dan Pengendalian Covid-19 - Hutahaean, Serri; Anggraini, Nourmayansa Vidya (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Coronavirus Disease 2019 or COVID-19 is a new disease that causes respiratory problems and pneumonia.This disease is caused by infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). TheCorona -19 virus is declared a world pandemic by WHO. The purpose of this study was to see the relationshipbetween student attitudes and actions in preventing and controlling Covid-19. This research method isdescriptive cross-sectional design. This research was conducted in May 2020 at the Faculty of HealthSciences, Universitas Pembangunan Nasional “Veteran” Jakarta. The research sample was 233 respondents.Data collection was carried out by distributing questionnaires using Google Doc Forms. The data obtainedwere then analyzed using SPSS with the chi-square test. The results showed p = 0.001 (p-value <0.05). Basedon the results of the analysis test, it can be denied that there is a significant relationship between studentattitudes and actions in preventing and controlling Covid-19. Therefore it is necessary to further research thefactors that prevent the prevention and control of COVID-19.